Deficit Consumption of Protein and Calcium on Children Aged 2-5 years old in Yogyakarta Indonesia - Syagata, Anindhita Syahbi; Dewi, Dian Alifah Kumala; Nugroho, Agung; Fauzia, Faurina Risca; Rohmah, Fayakun Nur; Khairani, Khalisa; Arifah, Siti (Journal of Global Nutrition, 2024)
In Indonesia, stunting cases are estimated to be a problem and some areas are likely to experience stunting due to its high prevalence including Yogyakarta Province. There are several causes of stunting, including a lack of macro and micronutrients. This study has objective to determine the relationship between protein and calcium intake in children aged 2-5 years height. This research was an analytical survey research with a cross-sectional approach. In this study, the primary data was collected using the SQ-FFQ questionnaire to determine the intake of protein and calcium. Stunting was measured using height for age (standard deviation). Subjects were 64 children as respondents and were distributed using a purposive sampling method. The data was processed with the help of SPSS software by performing multiple regression tests. In normal children, they tend to have higher average protein adequacy (111.1±84.5g) than stunted children (25.4±6.3g). Hence, the average calcium intake was 1707,3±1273,88mg in normal children and 291,2±253.8mg in stunted children. The results of the regression test explained that there was a significant relationship between children's height and protein and calcium intake (p<0.05). The relationship between protein and calcium intake with children's height is shown in the percentage of 10.3% and the other 89.7% is explained by variables outside the study. There is a significant relationship between protein and calcium intake with stunting and non-stunted children's height at the age of 2-5 years in Yogyakarta.